EDUCATION QUALITY AND ISSUES OF PEDAGOGICAL STAFF TRAINING - Vladimir P. Borisenkov (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is to reveal the reasons of deterioration of education quality at the Soviet and Post-Soviet school and, adopting the best experience of the countries that are recognised as world leaders in education; to plan the solution ways to current problems and situation at the Russian school. Methods. The principle of a historicism that expresses the necessity of concrete historical studying of the public phenomena is put in a basis of methodology of the research conducted by the author; it includes pedagogical phenomena (in the course of its origin), its development and transformation, taking into account variety of its communications, dependences and mediations. The concrete methods used in work, are typical for theoretical research: the analysis, an estimation and reduction in system of the empirical and generalised material on the selected theme. Large corpus of the scientific literature is studied. The data of the published international researches on education in which our country is widely involved (PISA, TIMSS), and also the national researches undertaken in the USA, Great Britain and other countries are considered. Methods of expert estimations, and direct supervision of educational process in secondary and higher educational institutions are applied. Results. The general characteristic of evolution of quality of the Russian education is presented during the Soviet and Post-Soviet periods. The factors which have had negative influence on quality of school training during the various periods are revealed. The estimation of the reasons which have caused failures of school reforms, carried out in the USSR in the 60-80s and within two last decades in modern Russia is given. The concurrent important positive shifts in this sphere, taking place in the same years are noted. Results of the international researches on education (PISA and TIMSS) are presented; the scoring of Russia among other states is defined, following the results of the testing of students revealing level of reading literacy, mathematical and natural-science competence. Scientific novelty. The author finds out the true reasons which have caused gradual decrease of quality indicators of education still long before disintegration of Soviet Union, aiming to overcome the settled representations and the stereotypes, concerning evolutions of school training quality in Russia. New elements of strategy of an education development in the countries which have become the powerful and leading nations in the given sphere are found out and considered based on the findings of the international researches. Practical significance. Perspective directions of preparation of the pedagogical personnel complying with the qualifying characteristics of modern requirements are allocated. Realisation of practical measures according to these directions and taking into account specificity of regions of Russia will promote training improvement of quality education in Russia that has the important strategic value for the future of our state.